Implementing a KKNI- and OBE-Based Curriculum in an Islamic Religious Education Study Program: A Case Study at STIT At-Taqwa Ciparay Bandung - Nurhayati Nurhayati; Imas Masruroh Imtihanah; Ela Komala; Muhammad Aditya Firdaus (MASI Mandiri Edukasi, 2026)
This study aims to analyze the implementation of the KKNI- and Outcome-Based Education (OBE) curriculum development policy in the Islamic Religious Education Study Program at STIT At-Taqwa Ciparay Bandung. A qualitative case study approach was employed. Data were collected through interviews, observations, and document analysis involving the Chairperson of STIT, the Head of the Islamic Religious Education Study Program, lecturers, and students. Data were analyzed using data condensation, data display, conclusion drawing, and verification. The findings show that the curriculum development policy has been implemented through the formulation of graduate profiles, graduate learning outcomes, curriculum structure, course distribution, and outcome-based semester lesson plans. Its implementation is supported by leadership commitment, institutional support, lecturer competence, a conducive academic culture, and the availability of curriculum documents. The main challenges include limited technical capacity in implementing OBE consistently across courses, insufficient learning facilities and resources, and the need to strengthen academic support systems. To address these challenges, the institution has conducted training, workshops, mentoring, curriculum revision, periodic evaluation, and stakeholder involvement. These efforts have strengthened alignment among learning outcomes, curriculum implementation, and quality assurance, demonstrating that curriculum implementation is continually improved through systematic institutional support.